Femoral neck stress fracture during sport climbing - Thomas Küpper; Steven Rutten; Audry Morrison; Volker Schöffl (Health Promotion & Physical Activity, 2021)
While the epiphyseal stress fracture of the finger’s middle phalanx is a known sport-specific injury occurring only in adolescent climbers, and in other locations it’s rare, no femoral neck stress fracture (FNSF) in sports climbing has yet been reported. An experienced female sport climber (37y, 160 cm, 45 kg, BMI 17.5) suffered from pain in the left inguinal region while climbing, and later, also required a stick to walk. Routine radiography missed the FNSF and it was many weeks before a MRI accurately provided that diagnosis. The time between the X-ray and MRI should have been minimized as it resulted in a delayed diagnosis, unnecessary pain and delayed healing. In this situation the initial clinical investigation, the patient’s history and the X-ray did not lead to a clear diagnosis, and the initial treatment was ineffective. Further investigation by MRI and / or CT scans should have taken place sooner and would have been essential.